Potret Penguasaan Microsoft Office Mahasiswa Administrasi Perkantoran Papua - Alienra Davry Nanda Kadun MT (Pusat Riset dan Inovasi Nasional, 2024)
The use of technology aligned with the principles of modern office administration. Cenderawasih university students in the department of Office Administration Management are equipped with computer technology skills, particularly Microsoft Office programs. This research aims to assess students’ skill in using Microsoft Office programs i.e. Microsoft Word, Microsoft Excel and Microsoft Power Point. This quantitative research uses test instruments given to active students in each year group. Results show that students' skill in using the three Microsoft Office applications is only at a low to moderate level. For specific application, namely Microsoft Excel, low and medium skill students were found almost equal in quantity. This research could be used as an evaluation for the university department to improve its student skills.